English Teachers in a Postwar Democracy : Emerging Choice in London Schools, 1945-1965 - Medway, Peter; Hardcastle, John.; Brewis, Georgina; Crook, David; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
Conflicting conservative and radical impulses in English society after WWII were played out in microcosm in education. They particularly shaped English teaching, examined in three post-war London schools in a detailed study that uses oral history interviews with former teachers and students and documents including mark books and students' work.
Keywords: History; Great Britain -- History; Democracy; Education; Higher education; Education -- History; Social sciences; History; History of Britain and Ireland; History of Education; Education, general; Higher Education; Democracy; Social Sciences, general